REDUKSI BAKTERI TOTAL COLIFORM DAN ESCHERICHIA COLI PADA AIR SUMUR DENGAN MENGGUNAKAN POT KERAMIK BERBAHAN SEKAM PADI DAN ZEOLIT - Masthura Masthura; Ratni Sirait; Nurul Rizki Amalia (Indonesian Physics Communication, 2023)
Well water has been tested using ceramic pots made from clay, rice husk and zeolite which aims to determine the effect of variations in the composition of materials in ceramic pots on reducing levels of total coliform and escherichia coli, as well as to determine the effectiveness of ceramic pots in reducing these bacteria. Variations in clay, rice husk and zeolite ceramic pot materials in the samples were A (60% : 20% : 20%), B (50% : 20% : 30%), and C (40% : 20% : 20%) with a sieve size of 100 mesh which is flowed with a batch system. The process of making ceramic pots is by burning for 8 hours at a temperature of 850°C – 900°C and producing ceramic pots with a height of 18 cm and a diameter of 21 cm. Total coliform with the highest efficiency of 96,15% and Escherichia coli with the highest efficiency of 100% for 152 hours and 136 hours. While the results of the research on the ceramic membrane sample B were able to reduce total coliform and Escherichia coli with the lowest efficiency of 64,10% within 120 hours.